Deroči vrelec Antona Krempla (University of Maribor Press, 2021)
Anton Krempl‘s Gushing Well.The monograph is devoted to the 230th anniversary of the birth of a major Slo‑venian priest, a poet, writer and national awakener Anton Krempl and the events taking place in Mala Nedelja related to his life and work. In the first half of the 19th century, Krempl was among few authors from East Styria who advocated for the unification of the Slovenian literary norm. Thus, he did not follow Dajnko’s idea that Slovenes in Styria, situated between Drava and Mura rivers, would develop their own literary norm. The monograph presents Krempl’s influence on the creation of Slovene literary norm in the mid‑19th century, analyses linguistic traits in his historic work Dogodivščine štajerske zemle (1845), and the use of verb forms and stylised expressions. The monograph also outlines an account of several periods of his stay and work in East Styria, as well as events contributing to the creation of his ethnic identity. The monograph informs the reader of Kremplov’s hagiographic stories Branje od tih v kmetičke kalendre postavlenih ino nekerih drugih svetnikov, as well as his manuscripts, held by Maribor University Library (UKM). The work analyses spoken language of Mala Nedelja in relation to Krem‑pl, presents an overview of his contemporaries, and presents the work of Anton Božič, one of the many propagators of Krempl‘s patriotic work.